Métis or Mixed: Contesting the Racialization of Métis Legal Identity in Daniels v. Canada - Martel, Karine (University of North Carolina at Chapel Hill, 2016)
Constitutions around the world are being revised. Indigenous Peoples are finally beginning to gain more recognition in these colonial rule books. Historically, Indigenous Peoples have rarely been mentioned at all in these founding documents, despite being the founding Peoples their countries. Today however, the very same documents that were once used to justify the discrimination of Indigenous Peoples, are striving to promote greater respect, rights, sovereignty and self-determination for First Peoples around the world. While Indigenous Peoples around the globe suffered from similar oppressions as a result of colonialism, the progress made to correct these wrongdoings is occurring at different rates. In Australia, it was not until 1962 that Aboriginals were given the right to vote under the Australian Constitution, and it was not until 1967 that they were included in censuses. Today, in Australia, there is a large push to remove certain constitutional provisions still capable of discriminating against Australian Aboriginals, and to include a preamble to the Australian Constitution that will recognize Aboriginals as the First Peoples of Australia. In the Scandinavian countries of Norway, Sweden, and Finland, recent constitutional amendments or parliamentary acts have allowed the Sami to establish their own parliaments. These parliaments seek to further Sami sovereignty and self-determination by allowing the Sami greater control over their own cultural and linguistic affairs and natural resources. But for an Indigenous group in Canada, the Métis, the struggle to be included in the Canadian constitution in a way that will promote respect and self-determination is an ongoing battle. The Métis are seeking the recognition as an Indigenous nation and the rights of self-determination and respect that come with such recognition. However, they are seeking to do so in a document that has long denied Metis’ status as an Aboriginal People and has perpetuated an incorrect understanding of the Metis. Bachelor of Arts